2019
DOI: 10.1111/anti.12543
|View full text |Cite
|
Sign up to set email alerts
|

Poverty in Transit: Uber, Taxi Coops, and the Struggle over Philadelphia's Transportation Economy

Abstract: This article examines how ride‐hailing companies like Uber have disrupted not only the mainstream taxi industry but also progressive efforts to remedy that industry's shortcomings. The article focuses on Alliance Taxi Cooperative (ATC), a failed taxi worker cooperative in Philadelphia. ATC was deeply committed to economic democracy, living wages, and outreach to underserved communities. Its ambitions were nevertheless thwarted by regulatory obstruction and market disruptions caused by Uber. Drawing on relation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
0
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(29 citation statements)
references
References 30 publications
0
26
0
3
Order By: Relevance
“…The gig economy is disrupting the traditional taxi industry worldwide (Borowiak 2019). Undifferentiated and commoditized kinds of work are most likely to be automated over time, and maybe performed by automated vehicles as some experts predict (Lieber and Puente 2016).…”
Section: Discussionmentioning
confidence: 99%
“…The gig economy is disrupting the traditional taxi industry worldwide (Borowiak 2019). Undifferentiated and commoditized kinds of work are most likely to be automated over time, and maybe performed by automated vehicles as some experts predict (Lieber and Puente 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Drawing on critical legal theory, our colleagues Bronwen Morgan and Declan Kuch (forthcoming), while aware of the extractive dynamics of platforms such as Uber and Airbnb, have been working with others in the legal pluralism tradition to specify the legal conditions of possibility for platform cooperativism and the role they might play in facilitating different forms of mobility, food security, production and repair of goods, peer to peer finance and care. There's nothing inherently capitalist about platforms -in fact a point Uber makes all the time when it insists its drivers are not wage employees (Borowiak, 2019). This contingency opens us to the possibility of a post-capitalist platform economy and here we would point to the work of the P2P foundation pushing this forward in practice around the world.…”
Section: What If It Didn't?mentioning
confidence: 94%
“…Still, only recently has it become symptomatic for a whole generation of workers and, as such, strongly debated in the academic literature (Kalleberg, 2009;2012;Rubery et al, 2018;Wilson and Ebert, 2013;Campbell and Price, 2016). Studies have shown that the platform economy increases wealth, racial, and gender inequality (Schor, 2017;Schor and Attwood-Charles, 2017;Barzilay and Ben-David, 2016;Kalleberg, 2013), leads to changes in job quality (Kalleberg, 2013;2012), deskilling and the loss of occupational identity (Borowiak, 2019), is a source of individual and social vulnerability, affecting personal and social lives (Wilson and Ebert, 2013), imposes isolation and psychological burdens, and demolishes work-life balance (Berg et al, 2018). In most cases, the platform economy does not impose any obligations on workers in terms of the time in which to conclude a task, however, sophisticated systems of surveillance control the workflow, evaluate and manage work activities (ibid.).…”
Section: Work On Lbpsmentioning
confidence: 99%